A multimedia library guide for general reference information - Zainab, Awang Ngah; Teh, Kang Hai; Hazita, Md Arip (SAGE Publications, 1999)
Decribed the development of a multimedia guide, University of Malaya Library Information System (UMLIS) to provide answers to general reference queries for the University of Malaya library. The guide was developed using Authorware 3.0. The guide provides information on all twelve libraries within the UM library system with details about the type of services, procedures for membership, borrowing, returning, reservation, fines, regulations, opening hours, facilities offered, the various collections, databases available on C-ROM and on the OPAC.